Reducing Residual Stresses in Synthetic Cast Iron by Ti Microalloying - Peter Futas; Janette Brezinová; Miroslav Pástor; Alena Pribulova (Metals)
During solidification and cooling of the castings, residual stresses are produced in the material. In technical practice, residual stresses are very important because, in addition to the operational loading, they can lead to material failure and, consequently, to equipment or structural failures. The accurate determination of residual stresses by numerical simulations presents a significant challenge due to the number of variables involved in modelling technological processes. Consequently, in many cases, residual stress levels are typically obtained using experimental measurements. Where possible, these measurements are complemented by monitoring and evaluating parameter changes that occur due to changes in the input conditions. In this paper, findings from experimental measurements of residual stresses in castings made from synthetic cast iron are reported, with a specific focus on the effect of titanium (Ti) microalloying on these residual stress levels. Comparison of the experimental results obtained from castings composed of grey cast iron shows that microalloying with titanium metal effectively reduces the residual stresses while maintaining the same tensile strength and Brinell hardness (HB). This highlights the potential benefits of microalloying in enhancing the benefits and reliability of cast iron materials.